Localized Structures and Turbulent Spectra in the Magnetopause. Issue 4 (5th April 2019) - Pathak, Neha; Uma, R.; Sharma, R. P.
Abstract: Kinetic Alfvén wave (KAW) and whistler wave play a key role in the framework of turbulence and reconnection. There are lot of observations of these wave in the magnetopause region. The present paper deals with the nonlinear evolution of KAW and a weak whistler wave through the preexisting magnetic reconnection site. For this study the dynamical evolution equations are derived by taking into account the ponderomotive force driven density modification and magnetic field fluctuations due to shear field modeled by the Harris sheet. Furthermore, these equations have been solved numerically as well as semianalytically. For numerical integrations we have used the pseudospectral method and finite difference method and for semianalytically Runge Kutta method. Simulated results have shown the evolution of coherent structures or current sheets, which are capable to energy transfer efficiently. These structures have scale size around ion gyroradius as well as electron inertial length as calculated analytically. At a later time the chaotic structures arise in this reconnection site. This gives the signature of turbulence generation. Therefore, the magnetic power spectrum with scaling is also presented in this manuscript and their relevance with the observed spectrum (calculated from the Cluster data (Chaston, 2008, https://doi.org/10.1029/2008GL033601 )) is also pointed out. Key Points: Role of KAW and Whistler waves in the reconnection site is very important A model is developed to study the effects of background Harris field and KAW nonlinearity in evolution of KAW and weak whistler wave in magnetic reconnection site Localized structures have scale sizes varying from ion gyroradious to electron skin depth